Piezoelectric energy harvesting and charging performance of Pb(Zn1/3Nb2/3)O3–Pb(Zr0.5Ti0.5)O3 nanoparticle-embedded P(VDF-TrFE) nanofiber composite sheets. (10th November 2018) - Liu, Kaihua; Choi, Hong Je; Kim, Byeong Kon; Kim, Da Bin; Han, Chan Su; Kim, Seung Won; Kang, Han Byul; Park, Jin-Woo; Cho, Yong Soo
Abstract: Piezoelectric composite structures have been studied to optimize energy harvesting and charging performance. Here, a specific piezoelectric composition of 0.4Pb(Zn1/3 Nb2/3 )O3 –0.6Pb(Zr0.5 Ti0.5 )O3 (PZN–PZT) has been selected for better energy harvesting performance. Different contents of PZN-PZT nanoparticles of ∼54 nm were embedded into a matrix of poly(vinylidene fluoride–trifluoroethylene) [P(VDF–TrFE)] by a single electrospinning process. The single-phase perovskite nanoparticles were initially prepared by combustion synthesis with the assistance of polyacrylic acid (PAA) as a fuel. The enhanced energy harvesting performance of flexible composite nanogenerators was ascertained by exhibiting ∼3.4 V output voltage and ∼240 nA output current for the 20 vol% nanoparticles-incorporated single sheet. The charging capability was found to be enhanced by designing the stacked nanofiber composite sheets in series, suggesting that the rate of charging and the saturation voltage are dependent on the number of composite sheets in series. For instance, the double stacked sheets exhibited a ∼5.7 V charging capability within ∼150 s.